An Update on Acute Pancreatitis - Catalin V. Ivan; James A. Stephenson; Vikas Shah; Kumaresan Sandrasegaran; Arumugam Rajesh (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
In recent years, there have been further advances in understanding of the acute pancreatic inflammation and its complications. Among these are emerging concepts such as peripancreatic necrosis and main duct injury secondary to necrotizing pancreatitis. To remain relevant to the clinical teams, radiologists need to be aware of these advances in knowledge and their reports should provide key points of information that may impact patient management. This article provides an up to date review of acute pancreatitis.